Laser-assisted additive technologies for the execution of dental restorative prostheses. Issue 1 (December 2020) - Moraru, E; Dontu, O; Rizescu, C; Spanu, A; Ciobanu, R; Draghici, C
Abstract: In the paper the authors present a technology with a great development perspective applied in restorative dental prosthetics based on the action of the laser. Also, there is presented an additive manufacturing method for obtaining dental prototypes from special materials, which can have multiple applications in the dental field. By this, dentists can replace the traditional outdated methods of prosthesis. A 3D printer for dentistry is a real opportunity to automate the most important stage in the work of dental laboratories, as well as move to a new level of quality. High productivity, waste-free production, possibility of realization of complex geometries - this is only a small part of the advantages of these technologies for metal and polymeric printing. The researches in this article even show that the prostheses made by selective laser melting have some better mechanical properties than the conventional casted prostheses from the same material.